(untitled) (Sebha University Conference Proceedings, 2024)
In order to lower electricity consumption, improve billing accuracy, and avoid customer issues, it is essential for residences, businesses, and factories to monitor their electrical meters. This paper introduces Zigbee technology as a standards-based wireless technology designed to facilitate low-power, low-cost wireless networks for the internet of things (IoT) and machine-to-machine (M2M). Zigbee is an open-source device for low-power, low-data-rate applications. Zigbee allows much lower data speeds and employs a mesh networking protocol. The goal of this work is to employ ZigBee networks to address earlier issues with electricity usage measurement. These networks eliminate the need for employees to carry out this procedure. Due to some technical and manufacturing issues with available reading meters, the practical portion of the work involved using an Arduino to simulate the operation of an electric meter. The reading has been successfully linked and transmitted, and a distance of 300 meters of transmission has been achieved via XBee. This confirms the process of using ZigBee networks to provide a wide and suitable network to monitor electrical meters in residential neighborhoods.